(untitled) (The Review of Diabetic Studies, 2025)
Quality in nursing care is a critical outcome determinant in the burn units, but a tremendous gap was observed in the objective assessment of the real clinical practices and determinants of the same in the Saudi Arabian healthcare setting. This research was done to assess the compliance of nursing practice with international practices and the completion of nurses in Saudi burn units. It was a cross-sectional, observational research study in two large tertiary hospitals under a census sample of 78 registered nurses. A validated observational checklist and self-reported questionnaire were used to collect data, and ANOVA, correlations, t-tests, multiple linear regression, and descriptive statistics were all used to analyze the data. The average practice adherence was 72.5% (SD=11.3), which is a moderate level of compliance. Burn training, burn unit experience, and level of education were significantly positively associated with adherence (p< 0.001). Importantly, the regression model (F(3,74) = 17.58, p < 0.001, Adj. R 2 =0.392) established formal training (B=4.98, p=0.010), experience (B=0.68, p=0.002), and education level (B=2.05, p=0.024) to be significant independent predictors. The study concludes that the adherence to practice is moderate, but certified burn care training investment turns out to be the most effective strategy to improve the quality of nursing and can be taken as clear evidence-based guidance on healthcare policy and professional development programs in the area.